Pengaruh Good Corporate Governance dan Sistem Pengendalian Intern Terhadap Penyalahgunaan Aset Dengan Kualitas Audit Intern Sebagai Variabel Moderasi - Savitri Savitri; Yudhi Herliansyah (Owner : Riset dan Jurnal Akuntansi, 2022)
This study aims to test whether good corporate governance, internal control system affects asset misappropriation with the quality of internal audits as a moderation variable. This research uses quantitative methods, namely using questionnaires. The sampling method used is a purposive sampling technique. In this study, a total sample of 105 respondents. The analysis methods in this study include descriptive statistical analysis, outer model test (measurement model), structural model test (inner model), and bootstrap hypothesis testing using Smart Partial Square (SmartPLS) path modeling method. The results of this study show that good corporate governance and internal control systems have a significant influence on asset misappropriation with the classification of pure moderation. Meanwhile, the quality of internal audits does not moderate good corporate governance and the internal control system for asset misappropriation with the classification of predictors of moderation. In bank operational practices, the more complex the risks faced by banks, the more the need for good corporate governance practices by banks. To minimize the occurrence of fraud, it is necessary to strengthen the internal control system in the form of implementing anti-fraud strategies by banks. Bank Mandiri has arranged in great detail the obligations of each position level and each head office and branch office. This is intended to minimize fraud and to protect customers.